Participation and Contract Choice in the Tenancy Market - Sharmina Ahmed; Christopher Findlay (Economics and Econometrics Research Institute (EERI), 2012)
Though sharecropping remains widespread, its determinants are still poorly understood and the debate over the extent of risk-sharing and moral hazard is far from settled. Moreover, existing empirical study very often plague by selection problem. We address both issues using data from rural Bangladesh. This paper tested a model empirically where the leasing decision and contract choice are simultaneous. A modified Heckman model is estimated which avoids the selectivity bias of observed contracts. Empirical tests reject the hypothesis of pure risk sharing and a wide range of support for the presence of moral hazard problem in the choice of contracts.
Keywords: Q15; 330; Contract choice; Heckman model; Moral hazard; Risk; Sharecropping